PATH-39. A 44-YEAR-OLD FEMALE WITH DICER1-MUTANT PRIMARY INTRACRANIAL SARCOMA WITH IMAGING NEAR END OF LIFE. (14th November 2022) - Lowman, Allison; Winiarz, Aleksandra; Bobholz, Samuel; Kyereme, Fitzgerald; Duenweg, Savannah; Coss, Dylan; Cochran, Elizabeth; Charlson, John; Connelly, Jennifer; LaViolette, Peter
Abstract: DICER1-mutant intracranial sarcomas were recently defined by WHO in the 2021 CNS tumor classifications. Currently there is a lack of literature describing the clinical nature of this disease. Here we present a case of primary intracranial sarcoma with DICER1 mutation and unknown etiology. A 44-year-old female presented with aphasia and right-sided weakness. Clinical imaging confirmed the presence of a hemorrhagic mass in the left frontal lobe and superior falx. The patient underwent two surgical resections, but a clear diagnosis was difficult to make due to heterogenous histological features and inconclusive genomic testing. The surgical samples were sent to the National Institute of Health where genetic testing indicated a DICER1 E1813D mutation with high allele frequency (97%), a TP53 mutation with high allele frequency (95%), and a high variant allele frequency NF1 splice site mutation (96%). This resulted in a diagnosis of DICER1-mutant primary intracranial sarcoma. The patient was treated with temozolomide, bevacizumab, and CPT-11. 382 days after the mass was originally identified, the patient died. A detailed analysis of the radiographic images was performed by creating T1-weighted post-contrast enhancement maps (T1C) and T2-weighted fluid attenuated inversion recovery (FLAIR) hyper-intensity maps for each timepoint. We plotted these volumes over time alongside the patient's treatment history. Large spikes in T1C and FLAIR volume were seen 4 days prior to initiation of temozolomide and 31 days after CPT-11 treatment was ended. At the final clinical MRI, both volumes were about 4 times greater than that of the initial scan. Despite this disease's aggressive nature, it can be difficult to accurately diagnose, due in part to very few studies investigating the clinical features of this rare tumor. With the addition of this diagnosis to WHO CNS5, future studies should examine the behavior of these tumors, aiding in earlier diagnosis and improvement of treatment guidance.